2016
DOI: 10.1002/2016ja022465
|View full text |Cite
|
Sign up to set email alerts
|

O+ ion beams reflected below the Martian bow shock: MAVEN observations

Abstract: We investigate a generation mechanism of O+ ion beams observed above the Martian bow shock by analyzing ion velocity distribution functions (VDFs) measured by the Suprathermal and Thermal Ion Composition instrument on the Mars Atmosphere and Volatile Evolution (MAVEN) spacecraft. In the solar wind near Mars, MAVEN often observes energetic O+ ion beams (~10 keV or higher). Accompanied with the O+ ion beam events, we sometimes observe characteristic ion VDFs in the magnetosheath: a partial ring distribution. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Jarvinen et al [, ] pointed out that the magnetic barrier is stronger on the + E hemisphere than on the − E hemisphere on the dayside, indicating that it can prevent pickup ions from more effectively precipitating in the + E hemisphere rather than in the − E hemisphere by deflecting them. Indeed, Masunaga et al [] reported that some pickup ions precipitating toward the Martian upper atmosphere are reflected back to the solar wind based on MAVEN observations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Jarvinen et al [, ] pointed out that the magnetic barrier is stronger on the + E hemisphere than on the − E hemisphere on the dayside, indicating that it can prevent pickup ions from more effectively precipitating in the + E hemisphere rather than in the − E hemisphere by deflecting them. Indeed, Masunaga et al [] reported that some pickup ions precipitating toward the Martian upper atmosphere are reflected back to the solar wind based on MAVEN observations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It was recently found that some of incident O + pickup ions are reflected in the Martian magnetosheath and return to the solar wind as a beam with energy of ~10 keV or higher [ Masunaga et al ., ]. In this paper, to evaluate the importance of the reflection of incident O + pickup ions, we statistically estimated a reflection ratio by calculating average inward and outward O + ion fluxes (>10 keV) above the Martian bow shock.…”
Section: Resultsmentioning
confidence: 99%
“…Since Masunaga et al . [] examined O + ion reflection features only in the magnetosheath, it is important to identify the reflection features in MPR and compare their occurrence frequency between the magnetosheath and MPR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations